A TABELA DE HONORÁRIOS DO CAU FRENTE À TEORIA DE MARKETING PARA PRECIFICAÇÃO - Trevisan, Ricardo; Ono, Rosaria; Barros, Gil (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Brazilian official fee schedule for architect and urbanism services sets some cost-based pricing methods. But strategic management theories show the core importance of pricing as one of the four main tools of marketing mix on brand positioning. Therefore cost-based pricing methods are widely condemned by such theories. The only Brazilian official method which diverges from cost-based pricing (property area based) also has weak connection between price and value. Consumer behavior research shows the pricing ranges: minimum price is usually defined by costs (cheaper than that means financial loss), and maximum price is given by client's perceived value (more expensive than that means trading losses). Within this context, it is necessary to understand the role of CAU/BR fee schedule, which seems to be a set of parameters for minimum price instead of a reference to final price.